The Harmonization and Religious Tolerance Living in West Java: A Socioreligious Study of Plural Society - Erba Rozalina; Maswani (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2022)
Diversity and plurality are closely related fact with Indonesia. This plural society may generate two potential social conditions: harmonization and social conflicts. This study supports Talcott Parson’s Structural-Functional Theory that a good social system in a society, both structural and functional, could preserve harmonization between religions. This study aims to explore a socio-religious condition in Kampung Sawah Bekasi and Cigugur village by analyzing kinds of harmonization and religious living tolerance within the community and exploring each leader's effort to improve the harmonization and tolerance of religious living in a plural society. This study also used a phenomenologist qualitative method which used interviews, observation and documentation as data-gathering techniques. The research found that the harmonization and toleranceof Kampung Sawah Bekasi and Cibubur village community in religious living prevails with three main assets. They are social, cultural, and kinship. These harmonizations and tolerance of the community religious living in both places manifest in their good relationship, high social intimacy, tight brotherhood, high empathy, and helping each other because of kinship. It is also because of the efforts and the active role within the community from all levels, the community, the regional government and local figures. The role of religious leaders also enhanced these harmonizations and tolerance in both places in West Java as the controller, leader, facilitator and motivator. They helped each other to prioritize unity.